Gambaran resiliensi mahasiswa psikologi penyintas perundungan kelompok sebaya - Darmaja, Sutya Niki; Wilani, Ni Made Ari (Jurnal Psikologi Udayana; Vol 8 No 2 (2021), 2021)
Bully is common case in every educational stage, including on college that involve college students.  Bullying on college can take place when there is a chance. Bullying can decrease the wellbeing of the college student who is being survived by bullying. Bullying can occur on any college student in any department. A case describing the bullying’s experience on psychology student that pointed out the survivor able to rise up from bullying experience and reach positive achievements. That case indicates the role of resilience. By that case, this study focused on exploring the resilience on bullying survivor. Psychology student were selected to obtain how survivor’s knowledge about psychology contribute to the develop resilience, and the ‘Psychology Student’ itself were a unique subject for this study. The subject criterions are an active psychology student, already pass minimum four semester, haven’t take an academic leave on the first second year lectures, and bullied for more than six months. This study using theoretical coding Strauss and Corbin to analyze the data. The result on this study is an overview of resilience on bullying survivor including the bullying experience, coping, adaptation, reaching out, and the role of psychology knowledge on survivor. This study is expected increasing knowledge about resilience on bullying survivor to other researcher, the survivor itself, and other parties that will make use of this study’s result in the positive way.